International Conference on Population and Development (ICPD) Programme of Action and climate action: an intersecting agenda - Angela Baschieri; Chiagozie Udeh (Sexual and Reproductive Health Matters)
2024 marked the 30th anniversary of the International Conference on Population and Development (ICPD) Programme of Action (PoA) held in Cairo in 1994, which coincided with the year that the United Nations Framework Convention on Climate Change (UNFCCC) went into force. Three decades later, these agendas have become increasingly interconnected and climate change has evolved into a climate crisis, as the world undergoes unprecedented demographic changes. How we deal with these unprecedented changes, and the timings of our shared actions, will define our future. This commentary reflects on the principles of the ICPD PoA and argues for their relevance in today’s fight for climate justice. To build a just and sustainable world, climate action must be guided by the aspirations of the ICPD PoA, promoting people-centred solutions, protecting human rights, advancing social justice, ensuring the right to health – including sexual and reproductive health and rights for all – and empowering women and youth in climate action and securing a future in which rights and choices are preserved for every individual.